Effect of Project-Based Learning Strategy on Students’ Interest and Performance in Science in Calabar Municipality, Cross River State - Anari, Mary Ideba; Neji, Hope Amba; Agube, Chukwu Chukwu (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2025)
This study investigated the impact of project-based learning on students’ interest and academic performance in science in Calabar municipality local government area of Cross River state. The study adopted a pre-test, posttest quasi-experimental research design. Two research questions and hypotheses guided the study. The sample comprised 150 SSII students drawn from a population of 2100 students in the study area. The research instrument was a researcher-made test, tagged Science Achievement Test(SAT), with a reliability estimate of 0.80 using Kuder-Richardson, R-20, and a student interest questionnaire with a reliability index of 0.70 using Cronbach's alpha reliability estimate. The da\ta collected were analysed using descriptive and ANCOVA statistical tools. The result revealed that there was statistically significant difference in the student’s academic achievement F(1, 146) = 29.85, p < 0.000.with a mean gain score of 52.35 and the level of interest of students on the concept taught F(1, 147) = 2.75, p < 0.000 in favour of those in PBL group with with a mean gain of 23.25. It is recommended that science teachers integrate project-based learning in the science classroom to enhance students' understanding of science concepts and stimulate interest in science.